PERCEPTIONS OF RURAL MICROFINANCE BENEFICIARIES IN MALAWI ON JOINT LENDING LIABILITY AND LOAN REPAYMENTS - PHIRI, LIMBANI MWAYIWAO (My University, 2013)
The Malawi government adopted microfinance with Joint Lending Liability (JLL) as an instrument of poverty alleviation especially in the rural areas where poverty is rampant. However, the government’s microfinance schemes are faced with the problem of high default rates despite incorporating JLL which seems to have enhanced repayment performance in other countries. The purpose of the study was to explore the perceptions of rural microfinance beneficiaries regarding the concept of JLL and how this affects loan repayment performance. The researcher undertook an exploratory qualitative research through in-depth interviews on a purposively selected sample of eight beneficiaries from Malawi Rural Development Fund (MARDEF) in Bvumbwe area of Thyolo district in Malawi. The study revealed that, rural microfinance beneficiaries in Malawi lack a proper understanding of the peer mechanism in JLL and this distorts their perception and behaviour as regards loan repayments. This stems from lack of proper education and training to the beneficiaries prior to loan disbursements. There is need for microfinance institutions to train and educate beneficiaries on the basic principles of JJL and how they relate to loan repayment performance in microfinance.
MM (P&DM) thesis
Keywords: Microfinance; Loan repayments